A modified gelcasting approach to fabricate microscale randomized 1–3 piezoelectric arrays. Issue 1 (January 2017) - Xie, Rui; Wang, Xiaofeng; Peng, Guowen; Xie, Tian; Zhang, Dou; Zhou, Kechao; Huang, Guoji; Wang, Guoping; Wang, Hongqing
Abstract: A modified gelcasting approach was used to fabricate the microscale randomized 1–3 piezoelectric array, which involves the in situ polymerization of hydantion epoxy resin and 3, 3′-Diaminodipropylamine (DPTA) in the lead zirconate titanate (PZT) suspensions with low viscosity and high solid loading. Rheological results demonstrated that the hydantion epoxy resin concentration had little effect on the viscosity of the premix solution, and therefore the optimized solid loading of the suspensions with 15.0 wt% resin could reach as high as 55.0 vol%. Weibull analysis also revealed that a more homogenous microstructure was obtained derived from the 55.0 vol% PZT suspension, where the Weibull modulus and the characteristic flexural strength reached the maximum value of 12.57 and 80.94 MPa. The excellent randomized piezoelectric pillar array with superior structural integrity and high fidelity was successfully fabricated.